KOREOGRAFI KRIDHA MANGGALA KARYA DWI MARYANI - DEBITA EMY RACHMAWATI; Matheus Wasi Bantolo (Institut Seni Indonesia Surakarta, 2020)
This research is a discussion about the dance Kridha Manggala by Dwi Maryani which was created based on the Javanese dance tradition of Surakarta and Poco-Poco dance. The problem in this study was the form and creation of this work. To discuss the issue using the thought of choreography according to Sal Murgiyanto, the category of contemporary dance based on tradition according to Matheus Wasi Bantolo, the form of the dish using the analysis of Janet Adshead, and the process of creation using thinking of Alma M Hawkins. The methods in this study are descriptive analytic with qualitative data, and use a choreographed approach.The results showed that this work is a work Dwi Maryani showed that there is a combination of two elements that are Java elements and the Poco-Poco. The second combination of this element makes a fierce idea for Dwi Maryani in creating the work of Kridha Manggala. The combination of these two elements can be seen in terms of motion, music, and costumes. The process of creating this work through stages, viewing, sensing, interning, imagining or imagination, tilling, and forming. Live through the exploration, improvisation, and composition stages. Keywords: Kridha Manggala, Dwi Maryani, choreography.